Resistance in Series Model for Ultrafiltration Xylose Reductase from Product Mixtures - Noor Suzana, Bakar; Mimi Sakinah, A. M. (AENSI Publisher, 2015)
This study investigates the fouling mechanism in ultrafiltration membrane during separation of xylose reductase from product mixtures. The Resistance - Jn - Series Model was used in order to identify the responsible hydraulic resistance. The resistance against the flux was assumed to be comprised as membrane hydraulic, adsorption, pore pugging and fouling resistance. The profile of total resistance and corresponding flux decline were calculated and compared with the experimental data. The result showed that adsorption resistance (Rad) was the main contributed the rate of flux decline. Moreover the significant organic fouling that contribute during xylose reductase separation revealed that the fouling potential was Rad > Rpp > RF. The measure flux recovery of filtration xylose reductase was 93%.